Carbon Stocks Mapping of Mangrove Forest in North Buton Indonesia using Combination of Landsat and ALOS PALSAR Images in the Perspective of Climate Change Mitigation. Issue 1 (March 2020) - Golok Jaya, La Ode Muh.; Yamin, Muhammad; Ningrum, Ika Purwanti; Safani, Jamhir; Wikantika, Ketut
Abstract: Mapping of carbon stocks, distribution and its changes become one of the important strategies in climate change mitigation. This study aims to map the carbon stocks of mangrove forests and analyze the changes using a combination of Landsat and ALOS PALSAR images in North Buton, South East Sulawesi Province, Indonesia. Carbon stocks in mangrove forests are known stores several times more than forests in the mainland. Mangrove forest at coast of North Buton is one of the largest area of mangrove forest in south east Sulawesi. The research conducted using backscatter coefficient of HH and HV polarization from ALOS PALSAR and Normalized Difference Vegetation Index (NDVI) from Landsat. The results showed that Landsat image provided information about the distribution, density and change of the carbon stocks during year 2001-2017 while ALOS PALSAR provided the volume of carbon stocks in this region.